The impact of post-contrast acute kidney injury on in-hospital mortality after endovascular thrombectomy in patients with acute ischemic stroke - Laible, Mona; Jenetzky, Ekkehart; Möhlenbruch, Markus Alfred; Bendszus, Martin; Ringleb, Peter A.; Rizos, Timolaos (Frontiers in neurology, 2021)
Background and Purpose Clinical outcome and mortality after endovascular thrombectomy (EVT) in patients with ischemic stroke are commonly assessed after three months. In patients with acute kidney injury (AKI), unfavorable results for three-month mortality have been reported. However, data on the in-hospital mortality after EVT in this population are sparse. In the present study, we assessed whether acute kidney injury (AKI) impacts in-hospital and three-month mortality in patients undergoing EVT. Material and Methods From a prospectively recruitung database, consecutive acute ischemic stroke patients receiving EVT between 2010 and 2018 due to acute large vessel occlusion were included. Post-contrast AKI (PC-AKI) was defined as an increase of baseline-creatinine of ≥0.5mg/dl or >25% within 48 hours after the first measurement at admission. Adjusting for potential confounders, associations between PC-AKI and mortality after stroke was tested in uni- and multivariate logistic regression models. Results 1.169 patients were included; 166 of them (14.2%) died during the acute hospital stay. Criteria for PC-AKI were met by 29 of patients (2.5%). Presence of PC-AKI was associated with a significantly higher risk for in-hospital mortality in multivariate analysis (OR 2.87, 95%-CI 1.16-7.13, p=0.023). Further factors associated with in-hospital mortality encompassed higher age (OR 1.03, 95%-CI 1.01-1.04, p=0.002), stroke severity (OR 1.05, 95%-CI 1.03-1.08, p<0.001), symptomatic intracerebral hemorrhage (OR 3.20, 95%CI 1.69-6.04, p<0.001), posterior circulation stroke (OR 2.85, 95%CI 1.72-4.71, p<0.001) and failed recanalization (OR 2.00, 95%CI 1.35-3.00, p=0.001). Conclusion PC-AKI is rare after EVT but represents an important risk factor for in-hospital mortality and for mortality within three months after hospital discharge. Preventing PC-AKI after EVT may represent an important and potentially life-saving effort in future daily clinical practice.